Mind-body therapies for sleep disturbance among patients with cancer: A systematic review and meta-analysis - Jing Han; Hui-Lin Cheng; Liu-Na Bi; Alex Molasiotis (Elsevier, 2023)
Objectives: To assess whether mind-body therapies (MBTs) are effective for relieving sleep disturbance among patients with cancer. Design: Systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: Seven English electronic databases were searched from the date of inception to September 2022. All RCTs that included adults (≥18 years) who were treated with mindfulness, yoga, qigong, relaxation, and hypnosis were screened. The outcome was subjective and/or objective sleep disturbance.The revised Cochrane tool (RoB 2.0) was applied to evaluate the risk of bias. The RevMan software was applied to assessed each outcome according different control groups and assessment time points. Subgroup analyses were performed according to different categories of MBTs. Results: Sixty-eight RCTs (6339 participants) were identified. After requesting for missing data from corresponding authors of included RCTs, 56 studies (5051 participants) were included in the meta-analysis. The meta-analysis showed a significant immediate effect of mindfulness, yoga, relaxation, and hypnosis on subjective sleep disturbance, compared with usual care or wait list control, and the effect of mindfulness lasted at least 6 months. For objective sleep outcomes, we observed significant immediate effects of yoga on wake after sleep onset and of mindfulness on sleep onset latency and total sleep time. Compared with active control interventions, MBTs had no significant effect on sleep disturbance. Conclusions: Mindfulness, yoga, relaxation, and hypnosis were effective in sleep disturbance severity reduction among patients with cancer at post-intervention, and the effect of mindfulness lasted at least 6 months. Future MBTs studies should apply both objective and subjective sleep measurement tools